TELAAH KRITIS ATAS KETENTUAN “PERDAGANGAN ORANG DALAM” (INSIDER TRADING) DALAM HUKUM PASAR MODAL INDONESIA - Muhamad Ashri (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
On of the legal protection for investors in capital market where the insider trading isprohibited. This article describes the regulation of prohibition in capital marketregulation in Indonesia from theoretical perspective and comparative withregulation and implementation the insider trading in the United States. The result ofanalysis concludes that regulation of insider trading in Indonesia capital market lawfocused on subjective element which insider trading actor has a duty to corporation.In theoretical perspective that regulation based on fiduciary duty theory, whereasregulation of insider trading in the United State focused on objective elementmisappropriation. In theoretical perspective misappropriation information based onmisappropriation theory. The weakness regulation of insider trading based onfiduciary duty theory as regulated in Indonesia law become the writer'sargumentation to recommend the approach from misappropriation theory toregulated insider trading in revised Act No 8 of year 1995 concerning the CapitalMarket.